The "Sales Agent" Problem: Effort Choice under Performance Pay as Behavior toward Risk - Nick Zubanov; Bram Cadsby; Fei Song (Institute of Labor Economics (IZA), 2017)
An investor's choice between safe and risky assets has long been seen as a behavior toward risk: more risk-averse investors buy more of the safe asset. Applying this intuition to incentive pay contracts, we develop a model and an experiment that show, in a very general setting, that the choice between work effort and leisure under given linear incentives depends on how the attendant financial risk interacts with effort. We find that if the risk multiplies with effort, risk-averse individuals work less, whereas under additive risk effort choice is little affected by risk preferences. Our findings complement the literature on worker selection into incentive pay contracts by showing that lower effort of the risk-averse is another type of behavior toward risk. Our study is relevant to practice as well, since many jobs, such as commission work, feature multiplicative rather additive risk.
Keywords: M52; 330; risk aversion; effort; incentives